Pengaruh Strategy Digital Marketing dan Service Quality Terhadap Keputusan Pembelian Online Store “Fasfashion” - Anggi Anggi Indriyanti; Syafrudin Arif Marah Manunggal (Economics and Digital Business Review, 2023)
The purpose of this research is: (1) to analyze and learn how each variable of the 9p digital marketing strategy on "Fasfashion" marketing has affected the online purchase decision of the "Fasfashion" online store, (2) to analyze and determine how service quality affects the "Fasfashion" online purchase decisions, (3) simulate the impact of a variable digital marketing strategy of 9p mix marketing and service quality on the online purchase decision of the "Fasfahion" store. Independent variables used are product marketing product, price, place, goods, people, process, physical evidence, consumption, & waste) and service quality. Whereas the dependent variable is the decision of the purchase. The sample was used by as many as 100 responders using the restrictive sampling method. Data was collected using primary data through the distribution of the questionnaires. Some tests are done that include validity tests, religious tests, classic assumptions tests, and linear regression analysis tests. The coefficient of determination simultaneously influences the purchase decision (Y) of 0,697 or 69,7%. While the remaining 30,3% is influenced by other variables not examined.